EcTI impairs survival and proliferation pathways in triple-negative breast cancer by modulating cell-glycosaminoglycans and inflammatory cytokines. (28th October 2020) - Lobo, Yara A.; Bonazza, Camila; Batista, Fabrício P.; Castro, Rodrigo A.; Bonturi, Camila R.; Salu, Bruno R.; de Cassia Sinigaglia, Rita; Toma, Leny; Vicente, Carolina M.; Pidde, Giselle; Tambourgi, Denise V.; Alvarez-Flores, Miryam P.; et al.
Abstract: Breast cancer is the most common malignant tumor among women worldwide, and triple-negative breast cancer is the most aggressive type of breast cancer, which does not respond to hormonal therapies. The protease inhibitor, EcTI, extracted from seeds of Enterolobium contortisiliquum, acts on the main signaling pathways of the MDA-MB-231 triple-negative breast cancer cells. This inhibitor, when bound to collagen I of the extracellular matrix, triggers a series of pathways capable of decreasing the viability, adhesion, migration, and invasion of these cells. This inhibitor can interfere in the cell cycle process through the main signaling pathways such as the adhesion, Integrin/FAK/SRC, Akt, ERK, and the cell death pathway BAX and BCL-2. It also acts by reducing the main inflammatory cytokines such as TGF-α, IL-6, IL-8, and MCP-1, besides NFκB, a transcription factor, responsible for the aggressive and metastatic characteristics of this type of tumor. Thus, the inhibitor was able to reduce the main processes of carcinogenesis of this type of cancer. Highlights: EcTI suppresses viability and cell proliferation in TNBC in vitro. EcTI blocks collagen I mediated by adhesion, migration, and invasion in TNBC cells. EcTI changes glycosaminoglycans pattern in TNBC cells. EcTI acts as an anti-inflammatory by inhibiting the cytokines IL-6, IL-8, and TGF-α. EcTI induces apoptosis in TNBC cells.